Logistics Digitalization and The Third-Party Logistics Blue-Collar Employees Performance: The Role of Paradoxical Leader Behavior - Ashraf, Muhammad Hasan; Triki, Anis; Yalçın, Mehmet Gökhan (Emerald, 2024)
Purpose – This study examines the impact of third-party logistics (3PL) supervisors’ paradoxical leader behavior (PLB) on the relationship between logistics digitalization and 3PL blue-collar employee performance. 3PLs often lag in digitalization due to blue-collar employees struggling with learning paradoxes, i.e. the tension between abandoning the known methods in favor of new ones. In such situations, 3PL supervisors play a crucial role in helping their subordinates manage these tensions. By incorporating a paradox theory lens, we propose that 3PL supervisors’ PLB acts as a supportive tool, motivating blue-collar employees to address learning paradoxes, thereby improving their operational performance. Design/methodology/approach – We conduct a scenario-based behavioral experiment in which participants assume the role of a package sorter in a fictional 3PL hub setting. Participants engage in a custom-designed package sorting game that mimics a real-life hub sorting operation. Findings – The results indicate that digitalization combined with supervisors’ PLB significantly improves bluecollar employee performance, with the most substantial improvement observed in the high digitalization and high PLB condition than all other conditions. Originality/value – Our research examines the impact of digitalization on blue-collar employees’ performance through a paradox theory lens. We demonstrate that 3PLs can maximize digitalization benefits by ensuring supervisors exhibit high PLB. Also, we introduce a package sorting game for researchers to conduct experiments related to digitalization and hub operations.
Keywords: Logistics Digitalization; Third-Party Logistics; Paradox Theory; Paradoxical Leader Behavior; Behavioral Experiment